WOMEN’S HOUSEHOLD AND POVERTY - Sriadi Setyawati (Universitas Negeri Yogyakarta, 2013)
Poverty means the unfulfilled basic needs (food, shelter, health and basic education). Nowadays, women can participate freely in society due to their advancement in education and occupation. Therefore, many women whose social status is household head don’t rely on men. Meanwhile, the social status of traditional women is still considered relying on men. The violence tends to occur in a poor woman household. Women have work hard and overtime in a poor woman household. The woman emancipation cannot make the status of man equal to woman. When the woman is oppressed, their creativity comes up. The poor women household tries hard to survive. In the worst condition, they often look for a loan and perform a simple life. This is the strategy to survive.Keywords: household, women, poverty